O magistério no século XXI: o trabalho de professor e as consequências pedagógicas em uma unidade educacional no Município de São Paulo - Dias, Dorotéa Bittencourt (2014)
This research was developed in order to explicate the structural role of labor in the human condition and the pedagogical implications, the social discourse about teacher educators work produces in the early grades of basic education in an educational unit of the Butantã's Regional Board Education in the municipality of São Paulo. The specific objective of this research was to demonstrate the consequences of (mis) valuation process of the teaching career today and indicate alternative proposals for this situation. Since only the commitment of teachers to work is not enough to ensure that the right learning happens. Through the analysis of working conditions, as well as in understanding the career choice for graduates, we find the view that teachers have the career of teaching and how they perceive the profession in the city of São Paulo during the first decade of this century. The study was conducted through desk research and analysis of semi structured interviews with five guiding questions, conducted with 10 elementary school teachers who demonstrated how these teachers share their professional experience and the difficulty in ensuring that all students have access to a teaching process and learning in its entirety. By analysis of the interviews we could see the view that teachers have the career of teaching and how they perceive the profession. We observe that the low self esteem of the teaching career brings significant damage for teachers, for students and for the country as a whole, since without the social value of the work of teacher and without the necessary structural conditions is not possible to ensure the required for access to dignity, respect and freedom essential to human relationships as a whole condition